1996
DOI: 10.1136/bmj.313.7063.987
|View full text |Cite
|
Sign up to set email alerts
|

Parents' difficulties and information needs in coping with acute illness in preschool children: a qualitative study

Abstract: Objectives-To identify and explore difficulties parents experience with acute illness in young children and the information they seek to help them.Design-Qualitative study using semistructured one to one and group interviews with parents of preschool children.Setting-Disadvantaged inner city community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
235
2
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(258 citation statements)
references
References 9 publications
14
235
2
2
Order By: Relevance
“…14,15 Further, seeking medical advice helps them to share the burden of responsibility. 14,15 Our study did suggest that the degree of fever phobia decreases as the child ages and the parent gains experience. Older parents, parents with older children, and parents with more children were less likely to seek medical attention for their febrile child.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14,15 Further, seeking medical advice helps them to share the burden of responsibility. 14,15 Our study did suggest that the degree of fever phobia decreases as the child ages and the parent gains experience. Older parents, parents with older children, and parents with more children were less likely to seek medical attention for their febrile child.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that fever makes parents fear that their child might be seriously ill and suffer irreparable harm. 14,15 Frequent checking of temperature and attempts to manage symptoms help parents maintain a sense of control and reduce feelings of helplessness. 14,15 Further, seeking medical advice helps them to share the burden of responsibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Irrespective of the ultimate diagnosis, the visibility, persistence, and perceived severity of symptoms are central to a parent's actions around help-seeking behavior 26 . Parents will notice a problem, but may not be able to judge the actual severity and need to seek expert advice 27 . In consultations with health professionals, parents often act as advocates for their sick child 26 , and have to balance being seen as responsible and vigilant against being labeled as overly neurotic, protective, or even exploitative.…”
Section: Sociocultural Factorsmentioning
confidence: 99%